Implementasi Literasi Baca Tulis Siswa Kelas Rendah Di Sekolah Dasar - I Ketut Satria Ardana; I Komang Agus Sukadana; I Komang Andi Suryawan; I Gusti Ngurah Agung Susila Sukajaya; Putu Nanda Prastika Priandana; I Putu Krishna Aditya; Basilius Redan Werang (Journal on Education, 2024)
The purpose of this research is to describe the implementation of literacy reading and writing students of class I in the Basic State School 2 Banjar Tegal, Buleleng district, buleleng-Bali. The research approach is qualitative research with the type of phenomenological research. This research data is a description of implementation the literature reading and written students of grade I in Basic state school 2 Banjer Tegal. The research instruments used are interview guidelines and documentation. The results of the study show that the student's literacy is in the developmental phase. As for the teacher's efforts in developing literacy, the following are: 1) When literacy hours are carried out especially for students with low literacy levels, the teacher invites the student to read the story first from the teacher, whether it's a folk story book, fairy tale or fiction. Then the teacher guides the students to recount the story that has been read by the class teacher in their own language. In the course of recounting the story content, the professor invites students to learn to read some of the pronouns from the contents of the story which makes it difficult for students to read, 2) the teacher uses the media of literature board made of board covered with plates as a place to paste pictures, letters and tribes. With the literacy board media, teachers easily introduce letters and pronouncements to the student whom the teacher first puts a picture on the literation board.